Preterm Birth: microbiological risk factors and sociodemographic markers. - Acero-Portilla, Paola (2022)
This review, as a class note, aims to determine the microorganisms that cause intrauterine infections considered as risk factors for spontaneous preterm birth in pregnant women with different demographic markers. The NCBI database was consulted. Research and literature review articles published from 2010 to 2019 were chosen, using the following terms: premature birth, pregnancy, risk factors, vaginal microbiome, microbiological data, sociodemographic determinants. The Mesh on Demand strategy was used, with which 18 studies were evaluated. Finally, as a result of the process, 11 articles were selected that studied the microbiological and demographic risk factors related to the outcome of premature birth in pregnant women. Currently, multiple events are known that can affect the normal course of a pregnancy, among these is preterm birth, a condition with a high incidence worldwide and that despite knowledge about the possible triggers, it has not yet been possible to reduce the statistics. The information that was found during the study of research papers and reviews in this field demonstrates that there are two main categories of risk factors, sociodemographic factors and microbiological factors. Among the microbiological factors, microorganisms that cause urinary and sexually transmitted infections, asymptomatic bacteriuria, and dysbiosis processes associated with bacterial vaginosis have been associated. In research that has studied sociodemographic and behavioral characteristics, maternal race-ethnicity, extreme maternal ages, maternal BMI, and socioeconomic status have been described as risk factors. That is why premature birth must be considered and treated as an entity of multifactorial etiology, which is why the need arises to propose new strategies in an intersectoral manner.